SOCIAL MEDIA MILITATES AGAINST DEVELOPMENT OF SELF DISCIPLINE FOR UNIVERSITY STUDENTS - Okpara, Mary (PEOPLE: International Journal of Social Sciences, 2017)
Social media have without doubts added to the on-the-spot interaction among people at close ranges and among those at different ends of the world. The success of modern day business, education and socialization of all sorts give much credit to the use of social media. However, the rate at which young adults love and use social networking is raising a concern. Indications abound that with their cell phones always connected to the Internet, they seem to be on the verge of addiction to the use of social media. So this article evaluates how much the simultaneous use of social media and receiving lectures has helped young adults in Nigerian universities improve their studies, develop their personalities and grow in emotional intelligence and balance. The article would more importantly study the long-term effect of the alleged youths’ addiction to social media on the struggle to develop self-discipline. Related literature on the topic under study would be explored to have a feel of scholarly opinions. Sampling interviews would equally be conducted on phone among some Nigerian university students. Theoretical framework on Internet addiction would be applied to find out why young adults could lose their bearing by, in spite of the benefits of, the use of social media. Suggestions would be made based on the process of the development of self-discipline and focused personality and their benefits in facing life challenges that would surely come.